Gastric cancer clinical characteristics and their altered trends in South China: An epidemiological study with 2,800 cases spanning 26 years - Wei, Hongfa; Zhan, Xiao-Yong; Liao, Xianying; Li, Wenchao; Chen, Hui; Deng, Cuncan; Jin, Xinghan; Huang, Zhangsen; Yang, Mo; Zhang, Changhua; He, Yulong (Frontiers in Oncology, 2023)
Gastric cancer (GC) is a serious threat to human health. Clinical GC characteristics in China may be impacted by changes in people's lifestyles and the promotion of early GC (EGC) screening. The present study aims to evaluate the recent trends of GC characteristics in South China and search for hazardous factors limiting the survival time of GC patients. Data of GC patients that were hospitalized in the Department of Digestive Center, the First Affiliated Hospital, Sun Yat-sen University, from 1994 to 2019 were collected and divided into two categories according to the time when the EGC screening began in China: the PRE (previous 13 years, 1994-2006) and the PAS group (past 13 years, 2007-2019). We found that though the 5-year survival rate increased in the PAS group compared to the PRE group(P<0.0001), patients with age ≥60 years or Borrmann type IV still had a worse prognosis. In the PAS group, the larger percentages of elderly patients and patients with Borrmann type IV in the lymphatic metastases (N1) group (41.0% vs. 51.1%, P=0.0014) and stage IV subgroup (20.7% vs. 32.2%, P=0.016), respectively, when compared to the PRE group, may have contributed to the poor outcome of GC. By comparing the odds ratio (OR) of 5-year overall survival (OS) in the two 13-year periods, females and T2 turned into risk factors because of a greater proportion of Borrmann type IV or elderly patients in the PAS group (OR=0.983, 95% CI 0.723-1.336 vs. OR=1.277, 95% CI 1.028-1.586; OR=1.545, 95% CI 0.499-4.775 vs. OR=2.227, 95% CI 1.124-4.271, respectively). Despite the GC epidemiology changes, the overall prognosis of GC patients has improved in South China, however, old age and Borrmann type IV are still the major restrictions affecting the survival of GC patients, which calls for additional attention.